GEN Z'S DIGITAL LIFE: SOCIAL MEDIA ACCOUNTS AS A MEANS OF OPEN AND HIDDEN EXPRESSION - Nizike Maiza Farin Ananta Purba; Zahra Putri Arifin; Muhammad Hafizh (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Generation Z grew up in a digital era that has made social media a primary platform for self-expression and identity formation. This study aims to describe Gen Z's overt and covert social media expression patterns and the factors that influence them. The method used was descriptive quantitative, with an online questionnaire conducted with 66 Gen Z respondents aged 15–25. The research results show that primary accounts are used to maintain social image, while alternate or anonymous accounts provide a more free and authentic space for personal expression. The dominant factors driving the use of secondary accounts are the need for privacy and the comfort of being authentic. This phenomenon illustrates that Gen Z has a flexible and dynamic digital identity that adapts to the audience's context. This research emphasizes the importance of digital literacy and self-identity awareness so that social media can be used healthily and responsibly.